On the Application of Information - Communication Technologies in the Development of Independent Creative Thinking of Youth - Mukhamedov, Gafurdjan Isroilovich; Makhmudova, Dilfuza Melievna (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the development of the creative ability of students of higher educational institutions. A version of the “problem” problem of mathematics is proposed, which allows stimulating students’ creative potential.